STRATEGY FOR INTRODUCING ALUE NAGA VILLAGE TOURISM THROUGH WEBSITE CREATION AS A DIGITAL PROMOTIONAL MEDIA USING GOOGLE SITES - Sufyan; Maimun; Munandar; Imilda; Muhammad Yassir; Riyan Maulana; Rahmat Arfan; Joharsah; Razaqul Daffa; Mujiburrahman (Jurnal Pengabdian Bangsa, 2025)
Community Service (PKM) is one of the activities carried out by universities or educational institutions to make a positive contribution to society. PKM focuses on the application of science and technology owned by universities to help solve problems faced by the community, and improve social welfare. Community Service (PKM) is also an effort to realize a more efficient education, namely education that is directly experienced by lecturers and students, so lecturers and students do not only get material, but what is more important is that the theories obtained in the lecture bench must also be applied in the field, especially in the community environment of Gampong Alue Naga, Syiah Kuala District, Banda Aceh City.